Comparative Clinical Effectiveness and Cost-Effectiveness of the Cochlear Osia System and Baha Attract System in Patients with Conductive or Mixed Hearing Loss or Single-Sided Deafness - Matthias Brunner; Manjula Schou; Robert J. Briggs; Dell Kingsford Smith (Journal of Market Access & Health Policy)
The aim of this study was to evaluate the comparative clinical effectiveness and cost-utility of the active transcutaneous Osia® System versus the passive transcutaneous Baha® Attract System for patients with conductive or mixed hearing loss or single-sided deafness in an Australian healthcare setting. In the absence of direct comparative evidence, an indirect treatment comparison (ITC) of the clinical effectiveness and utility gains was needed. The ITC was informed by three studies identified through a systematic literature review. A Markov model was developed to evaluate the cost-utility of the Osia System. The literature review identified three studies suitable to inform an ITC: Mylanus et al. 2020 and Briggs et al. 2022 (Osia System) and den Besten et al. 2019 (Baha Attract System). The Osia System was found to be clinically superior to the Baha Attract System, across objective audiological outcomes resulting in a clinically meaningful utility benefit of 0.03 measured by the Health Utility Index with at least equivalent safety. In conclusion, the Osia System is more effective than the Baha Attract System, providing better hearing and health-related quality of life outcomes. In an Australian healthcare setting, the Osia System is cost-effective as demonstrated in a cost-utility analysis versus the Baha Attract System.